القيم الأخلاقية مع الآخر بين الديانات السماوية الثلاثة وانعكاساتها الواقعية. -دراسة تحليلية مقارنة- - جواد, خديجة (University of Eloued جامعة الوادي, 2020)
لخص: تحتل القيم الأخلاقية أهمية كبيرة ضمن المنظومات الدينية، لا تقل أهمية عن النظم العقدية والتشريعية في الأديان، وبناء على أنّ النسيج الانساني متنوع الانتماءات الدينية والعقدية، ولا يمكن للعلاقات الانسانية أن تبنى على القطيعة والصراع، فكان لضبط العلاقة مع الآخر ضرورة واقعية وتحدي أمام الديانات، ولهذا لم تهملها الأديان منذ ظهورها، فالتشريعات الدينية لم تبق علاقات الإنسان بغيره الذي لا ينتمي إلى إطاره الديني بدون تنظيم، وإنما كانت المنظم والمؤطر لها ضمن قيم أخلاقية محددة، تضبط العلاقات الإنسانية مهما اختلفت المعتقدات، كما كان لها انعكاس عميق وظاهر عبر تاريخ الشعوب وفي واقعنا المعاصر. Abstract: The ethical values with the other have a great importance in the religious systems, and no less important than the doctrinal and legislative systems of religions. And based on the fact that the human construction has a variety of religious and belief affiliations, and human relations cannot be based on estrangement and conflict, so controlling the relationship with the other was a realistic necessity and a challenge in front of religions, and that is why religions have not neglected it since its emergence. Religious legislation did not keep human relations with others who did not belong to their religious framework without organization, Rather, it was the organizer and framer for it within specific moral values that regulate human relationships regardless of the differences in beliefs, and they have a deep and visible reflection in throughout the history of peoples and our contemporary reality.
مقال